PEMIKIRAN PENDIDIKAN MUHAMMAD ABDUH DAN PROSES MODERNISASI PESANTREN DI INDONESIA - Saifuddin Qudsi (Dirosat : Journal of Islamic Studies, 2016)
Muhammad Abduh is one of Salaf-Sufism figure who has rational Islamic concept in modern era. He was a reformer rational concept. He said that muslim’s deterioration happened because of muslim was contaminated by unbending (jumud) in many aspects; language, Islamic law (syariah), faith and society system. For Islamic context in Indonesia, Abduh’s concept has placed important role of Islamic history in Indonesia. For example, Muhammadiyah organization. It is the proof and the result of Muhammad Abduh’s reformism in islam. As the admiration to Muhammad Abduh, Ahmad Dahlan as the founder of Muhammadiyah, include Muhammad Abduh’s concept in curriculum of Muhammadiyah Schools, especially in Risalah Tauhid.